Gradient gradient powder material as well as preparation method and application thereof
Through the design of gradient gradient powder material and magnetron cosputtering technology, the problem of low bonding strength between non-metal and metal-based materials is solved, and performance improvement in high temperature and high pressure environments is achieved, especially the enhancement of mechanical strength and fatigue resistance.
Patent Information
- Application Number
- CN202510512082.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2025-08-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional non-metallic and metal-based materials have low bond strength and unstable overall performance. Especially under high temperature, high pressure and extreme conditions, the thermal conductivity, mechanical strength and thermal shock properties of the materials are insufficient.
Gradient gradient powder materials, including non-metallic cores, transition layers and modification layers, are used to form gradient layers through magnetron cosputtering technology, combining carbon materials with transition layer materials and modification layer materials to optimize interface performance.
It significantly enhances the bonding strength and overall performance of the material, improves mechanical strength, fatigue resistance, wear and corrosion resistance, is suitable for high temperature and extreme environments, and extends service life.
Smart Images

Figure CN120394861A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of powder preparation, and particularly relates to a gradient-varying powder material, a preparation method thereof, and an application thereof. Background Art
[0002] The combination of non-metallic powder and metal composite material combines the high hardness, wear resistance, and corrosion resistance of inorganic powder, as well as the toughness and conductivity of metal, and is widely used in fields such as aerospace, automotive, electronics, and machinery. However, due to the large differences in crystal structure and chemical properties between non-metallic powder and metal, and the large differences in thermal expansion coefficients of metals, the combination between traditional non-metallic and metal-based materials often has problems such as low bonding strength and unstable overall performance. Since the bonding strength of the material directly affects its use performance, a powder material with excellent bonding strength to metal-based materials is needed. At the same time, under high temperature, high pressure, and extreme conditions, the thermal conductivity, mechanical strength, and thermal shock performance of the material are also key factors to consider. Summary of the Invention
[0003] Aiming at the deficiencies of the prior art, the first object of the present invention is to provide a gradient-varying powder material. The gradient-varying powder material provided by the present invention exhibits excellent strength-ductility synergy, high fracture toughness, and enhanced anti-fatigue, wear, and corrosion capabilities, has good wettability with metals, can effectively strengthen the metal matrix and improve the performance of the metal matrix. In addition, it can also be well dispersed in resins, greatly improving the performance of resin-based composite materials.
[0004] The second object of the present invention is to provide a preparation method of a gradient-varying powder material.
[0005] The third object of the present invention is to provide an application of a gradient-varying powder material.
[0006] In order to achieve the above objects, the present invention adopts the following technical solutions:
[0007] The present invention provides a gradient-varying powder material, which sequentially includes a non-metallic core, a transition layer, a gradient layer, and a modification layer from the inside to the outside.
[0008] The non-metallic core is selected from at least one of diamond, graphite, graphene, and carbon nanotubes;
[0009] The gradient layer is composed of a transition layer material and a modification layer material, and the transition layer material gradually decreases from the inside to the outside, while the modification layer material gradually increases.
[0010] The transition layer material is selected from at least one of Ti, Zr, V, Ta, Nb, W, Mo, Cr, Mn, and B;
[0011] The modifying layer material is selected from at least one of Cu, Al, Ag, Mg, Zn, Ni, Co, Sn, and Cr.
[0012] The gradient-gradient powder material provided by the present invention uses a carbon material as the core material. First, a transition layer material is provided on its surface. The transition layer material has a strong carbide-forming ability, can form a stable compound interface with carbon atoms on the carbon-based surface, and the formed carbide has good chemical stability. At the same time, its lattice constant and thermal expansion coefficient are close to those of the carbon material, which is beneficial to reducing interface stress and the generation of stress. The modifying layer material is selected from metals with excellent functionality, such as conductivity / anti-corrosion / wear resistance, thermodynamic compatibility, mechanical buffering ability, and excellent bonding force with metal-based or resin-based materials. Combining with the gradient layer composed of the transition layer material and the modifying layer material further improves the overall performance of the coating, reduces interface stress concentration, and improves the bonding performance between the non-metallic core and the entire coating. Compared with homogeneous metals and alloys, the gradient-gradient powder material provided by the present invention exhibits unprecedented mechanical properties, including excellent strength-ductility synergy, high fracture toughness, and enhanced fatigue, wear, and corrosion resistance.
[0013] In a preferred embodiment, the non-metallic core is diamond;
[0014] The transition layer material is W;
[0015] The modifying layer material is Cu.
[0016] When the gradient-gradient powder material uses diamond as the non-metallic core, W as the transition layer material, the gradient of W and Cu as the gradient layer, and Cu as the modifying layer material, the oxidation temperature is significantly increased compared to pure diamond powder. Moreover, as a reinforcing material for copper-based materials, it can significantly improve the mechanical strength and thermal shock performance of copper-based composites. Therefore, it can not only expand the use temperature range of the material but also be used in harsh environments with large thermal shocks, significantly increasing the service life.
[0017] In a preferred embodiment, the non-metallic core is graphite powder;
[0018] The transition layer material is Mo;
[0019] The modifying layer material is Cu.
[0020] When the gradient-gradient powder material uses graphite powder as the non-metallic core, W as the transition layer material, the gradient of W and Cu as the gradient layer, and Cu as the modifying layer material, the oxidation temperature is significantly increased compared to graphite powder, and the application field range of graphite powder as a reinforcing body can be significantly expanded.
[0021] Preferably, the diameter of the non-metallic core is 5 - 800 μm, the thickness of the transition layer is 10 - 500 nm, the thickness of the gradient layer is 50 - 800 nm, and the thickness of the modification layer is 1 - 10 μm.
[0022] In the present invention, the thickness of each layer needs to be effectively controlled so that the performance of the gradient powder material is optimal. If the transition layer is too thin, the coverage is incomplete, and defects such as pinholes may occur, resulting in insufficient interfacial bonding strength. If the transition layer is too thick, the internal stress increases, peeling is likely to occur, and the interfacial thermal resistance increases, affecting properties such as thermal conductivity. If the gradient layer is too thin, the bonding strength is insufficient, the stress between the two materials cannot be effectively relieved, and peeling is likely to occur; the ideal performance gradient transition cannot be achieved, affecting the overall coating performance. If the gradient layer is too thick, the internal stress increases, the risk of cracking increases; the preparation cost increases; the adhesion decreases, and delamination may occur, affecting the overall coating performance.
[0023] The present invention also provides a method for preparing a gradient powder material. The non-metallic powder is pretreated to obtain the pretreated non-metallic powder, and then a transition layer is provided on the surface of the pretreated non-metallic powder. Then, a gradient layer is formed by magnetron co-sputtering on the surface of the transition layer using a transition layer material target and a modification layer material target, and finally a modification layer is provided on the surface of the gradient layer.
[0024] Preferably, the process of pretreating the non-metallic powder is as follows: first, the non-metallic powder is ultrasonically cleaned, and then the surface is plasma-activated.
[0025] Further preferably, the frequency of the ultrasonic cleaning is 10 - 60 kHz, the temperature is 40 - 80 °C, and the treatment time is 5 - 30 min.
[0026] Further preferably, during the plasma activation, at least one of Ar, O2, and H2 plasmas is used, the power is 100 - 400 W, the temperature is 100 - 400 °C, and the treatment time is 10 - 45 min.
[0027] In the present invention, the stains on the surface of the core material are removed by ultrasonic cleaning, and then the surface is further cleaned, and the surface energy of the core material is increased, enhancing its adhesion to the coating.
[0028] Preferably, the preparation method of the transition layer is selected from one of magnetron sputtering, evaporation plating, and ion plating.
[0029] In a preferred embodiment, during the process of forming a gradient layer by magnetron co-sputtering, the distances between the substrate and the target materials of the transition layer and the modification layer are both 10 - 25 cm, the flow rate of argon gas introduced is 10 - 50 sccm; the vacuum degree is 0.1 - 1.0 Pa, the swing speed of the substrate workpiece table is 30 - 60 r / min, and the vibration frequency is 10 - 40 Hz.
[0030] The inventor found that controlling the parameters during the process of forming a gradient layer by magnetron co-sputtering within the above ranges results in the optimal performance. If the working air pressure is too high or too low, it will affect the ion bombardment energy, leading to a decrease in the bonding force; improper control of the substrate temperature will affect the atomic migration ability and the uniformity of the composition distribution; inappropriate substrate rotation speed and vibration frequency will cause non-uniform local deposition.
[0031] During the actual operation process, two or more target materials are placed in the target device of the magnetron sputtering equipment, and the relative position with respect to the workpiece is face-to-face. In a vacuum inert gas environment, a certain rotation speed and temperature are adjusted, and the power of two or more target devices is controlled. The target materials are sputtered onto the surface of the workpiece. However, if the target material position arrangement is unreasonable, it will lead to non-uniform deposition; inappropriate distance between the substrate and the target material will affect the composition distribution; in the present invention, the distances from the two target materials to the substrate are equal, and the two target materials form a certain angle facing the substrate. The distance between the target material and the substrate is 10 - 25 cm to ensure the uniformity of sputtering.
[0032] In a preferred embodiment, during the process of forming a gradient layer by magnetron co-sputtering, first set the power of the transition layer target material to 50 - 500 W, and then decrease it at a linear speed of 5 - 20 W / min until the power of the transition layer target material is 0. First set the power of the modification layer target material to 0, and then increase it at a linear speed of 5 - 16 W / min until the power of the modification layer target material is 40 - 400 W. The time of magnetron co-sputtering is 5 - 25 min, and the time of the power overlap region is 1 - 3 min.
[0033] In the initial stage, only the sputtering of the transition layer target material is started, so that the transition layer material is first deposited on the surface of the substrate to form a good bonding foundation. Then, in the gradient stage, by precisely controlling the power changes of the two target materials, the deposition rates of the two materials show opposite trends of change: the deposition rate of the transition layer material gradually decreases, and the deposition rate of the modification layer material gradually increases; this opposite change causes the composition ratio of the two materials to gradually change during the film growth process, thus naturally forming a gradient structure.
[0034] In the present invention, the gradient power needs to be effectively controlled. If the power change rate is too fast, it will lead to a composition mutation and lose the gradient effect; improper control of the power ratio of the two targets will cause non-uniform composition distribution; power fluctuations will cause non-uniform local composition, and improper control of the sputtering time will affect the thickness of the gradient layer and the overall performance.
[0035] In a preferred embodiment, the gradient layer is heat-treated, and finally a modification layer is provided on the surface of the heat-treated gradient layer; the temperature of the heat treatment is 100-900°C, preferably 700-900°C, and the time of the heat treatment is 10-90 min. The inventors found that by heat-treating the obtained gradient layer, the interfacial bonding performance can be further improved, and the performance improvement is more significant when the heat treatment is carried out after the gradient layer compared to after the preparation of the modification layer.
[0036] In a preferred embodiment, the preparation method of the modification layer is selected from one of magnetron sputtering, evaporation plating, ion plating, electroless plating, and electroplating.
[0037] The present invention also provides an application of the gradient powder material, which is characterized in that: the gradient powder material is compounded with a metal matrix or a resin matrix and then applied as one of an electronic device heat dissipation material, a high-speed cutting tool material, an abrasive and grinding tool material, and a high-temperature protection material.
[0038] Principle and advantages
[0039] Through processes such as particle size control, sputtering preparation, and gradient combination, the present invention realizes the enhancement of the bonding strength between the powder material and the metal matrix material, improves the overall performance and reliability, realizes the gradient change property of the material, and thus improves its overall performance and reliability. Compared with homogeneous metals and alloys, these gradient-structured metals and alloys exhibit unprecedented mechanical properties, including excellent strength-ductility synergy, high fracture toughness, and enhanced resistance to fatigue, wear, and corrosion. Brief description of the drawings
[0040] Figure 1 , Schematic diagram of the gradient powder material. Detailed description of the invention
[0041] Example 1
[0042] In this example, diamond powder is used as the core material, tungsten is used as the transition layer material, and copper is used as the modification layer material.
[0043] The diamond powder with a particle size of 550 μm is ultrasonically cleaned to remove surface contaminants. When ultrasonically cleaning the powder, a frequency of 60 kHz, a temperature of 60°C, and a treatment time of 10 min are used; then the surface is activated by plasma cleaning. When performing plasma activation treatment, Ar and H2 gas plasmas are used, the power is 300 W, the temperature is 200°C, and the treatment time is 20 min; then a transition layer with a thickness of 200 nm is provided on the surface of the pretreated 550 μm diamond powder by magnetron sputtering.
[0044] Next, place the diamond powder containing the transition layer in the target device of the magnetron sputtering equipment. The target materials of the transition layer and the modification layer are also placed in the target device of the magnetron sputtering equipment, with a facing position relative to the workpiece. The flow rate of argon is 20 sccm; the vacuum degree is 0.4 Pa, the swing speed of the substrate workpiece table is 40 r / min, and the vibration frequency is 30 Hz. First, set the power of the transition layer target to 300 W, and then decrease it at a linear speed of 20 W / min until the power of the transition layer target is 0. First, set the power of the modification layer material target to 0, and then increase it at a linear speed of 10 W / min until the power of the modification layer material target is 150 W. The time of magnetron co-sputtering is 15 min, and the time in the power overlap region is 2 min to obtain a gradient layer with a thickness of 300 nm. Then, heat-treat the powder after obtaining the gradient layer. The heat-treatment temperature is 850, and the heat-treatment time is 30 min. Finally, a modification layer with a thickness of 2 μm is set on the pretreated gradient surface by electroplating.
[0045] The gradient powder material provided by the present invention has a 25% increase in the oxidation temperature compared to pure diamond powder. The initial oxidation temperature of diamond is 760 °C; the gradient powder material provided in this embodiment is increased to 950 °C, and the wetting angle with metal is 0.
[0046] Example 2
[0047] In this embodiment, diamond powder is used as the core material, tungsten is used as the transition layer material, and copper is used as the modification layer material.
[0048] Ultrasonically clean the diamond powder with a particle size of 300 μm to remove surface contaminants. When ultrasonically cleaning the powder, use a frequency of 60 kHz and a temperature of 60 °C, and the treatment time is 10 min; then activate the surface by plasma cleaning. When performing plasma activation treatment, use Ar and H2 gas plasmas, with a power of 300 W, a temperature of 200 °C, and a treatment time of 20 min; then set a transition layer with a thickness of 200 nm on the surface of the pretreated 550 μm diamond powder by magnetron sputtering.
[0049] Next, place the diamond powder containing the transition layer in the target device of the magnetron sputtering equipment. The target materials of the transition layer and the modification layer are also placed in the target device of the magnetron sputtering equipment, facing the workpiece directly. The flow rate of argon gas is 20 sccm; the vacuum degree is 0.4 Pa, the swing speed of the substrate workpiece table is 40 r / min, and the vibration frequency is 30 Hz. First, set the power of the transition layer target to 500 W, and then decrease it at a linear speed of 20 W / min until the power of the transition layer target is 0. First, set the power of the modification layer material target to 0, and then increase it at a linear speed of 16 W / min until the power of the modification layer material target is 400 W. The time of magnetron co-sputtering is 25 min, and the time of the power overlap area is 3 min to obtain a gradient layer with a thickness of 600 nm. Then, heat-treat the powder after obtaining the gradient layer. The heat treatment temperature is 800, and the heat treatment time is 30 min. Finally, set a modification layer with a thickness of 2 μm on the gradient surface after heat treatment by electroplating; obtain the diamond powder-metal matrix composite. Its thermal shock resistance is -50 - 150 °C, 100 cycles, and the performance only decreases by 0.1%. Compared with the untreated diamond powder-metal matrix composite with a thermal shock resistance of -50 - 150 °C and 100 cycles, the performance decreases by 10%. Obviously, it can be seen that after the gradient powder material provided in this embodiment enhances the copper matrix, compared with directly enhancing the copper matrix with diamond powder, the thermal shock resistance is greatly improved.
[0050] Example 3
[0051] In this embodiment, graphite powder is used as the core material, molybdenum is used as the transition layer material, and copper is used as the modification layer material.
[0052] Ultrasonically clean the graphite powder with a particle size of 250 μm to remove surface contaminants. When ultrasonically cleaning the powder, use a frequency of 20 kHz, a temperature of 60 °C, and a treatment time of 10 min; then activate the surface through plasma cleaning. When performing plasma activation treatment, use Ar and H2 gas plasmas, with a power of 300 W, a temperature of 200 °C, and a treatment time of 20 min; then set a transition layer with a thickness of 200 nm on the surface of the pretreated 550 μm diamond powder by magnetron sputtering.
[0053] Next, place the diamond powder containing the transition layer in the target device of the magnetron sputtering equipment. The target materials of the transition layer and the modification layer are also placed in the target device of the magnetron sputtering equipment, facing the workpiece directly. The flow rate of argon gas is 20 sccm; the vacuum degree is 0.4 Pa, the swing speed of the substrate workpiece table is 40 r / min, and the vibration frequency is 30 Hz. First, set the power of the transition layer target to 400 W, and then decrease it at a linear speed of 20 W / min until the power of the transition layer target is 0. First, set the power of the modification layer material target to 0, and then increase it at a linear speed of 15 W / min until the power of the modification layer material target is 300 W. The time of magnetron co-sputtering is 20 min, and the time in the power overlap region is 3 min to obtain a gradient layer with a thickness of 400 nm. Then, heat-treat the powder after obtaining the gradient layer. The heat-treatment temperature is 700, and the heat-treatment time is 30 min. Finally, set a modification layer with a thickness of 2 μm on the gradient surface after heat-treatment by electroplating; the initial oxidation temperature of the obtained graphite powder is increased by 20%, and the initial oxidation temperature of graphite is 400 °C; the gradient gradient powder material provided by the present invention is increased to 480 °C, and its wetting angle with the metal is 0.
[0054] Comparative Example 1
[0055] Other conditions are the same as those in Example 1, except that no transition layer is made, resulting in poor bonding force of the powder surface coating and easy film peeling.
[0056] Comparative Example 2
[0057] Other conditions are the same as those in Example 1, except that the transition layer is too thin, resulting in poor bonding force of the powder surface coating and easy film peeling.
[0058] Comparative Example 3
[0059] Other conditions are the same as those in Example 1, except that no gradient layer is made, resulting in easy generation of internal stress in the powder and easy film peeling.
Claims
1. A gradient-varying powder material, characterized in that: The gradient-gradient powder material sequentially includes a non-metal core, a transition layer, a gradient layer, and a modification layer from the inside to the outside. The non-metal core is selected from one of diamond, graphite, graphene, and carbon nanotubes. The gradient layer is composed of a transition layer material and a modification layer material. From the inside to the outside, the gradient of the transition layer material decreases, and the gradient of the modification layer material increases. The transition layer material is selected from at least one of Ti, Zr, V, Ta, Nb, W, Mo, Cr, Mn, and B. The modification layer material is selected from at least one of Cu, Al, Ag, Mg, Zn, Ni, Co, Sn, and Cr.
2. A gradient-gradient powder material according to claim 1, characterized in that: The non-metal core is diamond. The transition layer material is W. The modification layer material is Cu.
3. A gradient-gradient powder material according to claim 1, characterized in that: The non-metal core is graphite. The transition layer material is Mo. The modification layer material is Cu.
4. A gradient-varying powder material according to any one of claims 1-3, characterized in that: The diameter of the non-metal core is 5 - 800 μm, the thickness of the transition layer is 10 - 500 nm, the thickness of the gradient layer is 50 - 800 nm, and the thickness of the modification layer is 1 - 10 μm.
5. The preparation method of a gradient-varying powder material according to any one of claims 1-4, characterized in that: The non-metal powder is pretreated to obtain the pretreated non-metal powder, then a transition layer is provided on the surface of the pretreated non-metal powder, and then a gradient layer is formed by magnetron co-sputtering on the surface of the transition layer using a transition layer material target and a modification layer material target, and finally a modification layer is provided on the surface of the gradient layer.
6. The preparation method of a gradient-varying powder material according to claim 3, characterized in that: The process of pretreating the non-metal powder is as follows: first, the non-metal powder is ultrasonically cleaned, and then plasma cleaning is performed to activate the surface. The frequency of the ultrasonic cleaning is 10 - 60 kHz, the temperature is 40 - 80 °C, and the treatment time is 5 - 30 min. When performing plasma activation, at least one of Ar, O2, and H2 plasmas is used, the power is 100 - 400 W, the temperature is 100 - 400 °C, and the treatment time is 10 - 45 min.
7. The preparation method of a gradient-varying powder material according to claim 5, characterized in that: During the process of forming the gradient layer by magnetron co-sputtering, first, the power of the transition layer target is set to 50 - 500 W, and then it is decreased at a linear speed of 5 - 20 W / min until the power of the transition layer target is 0. First, the power of the modification layer material target is set to 0, and then it is increased at a linear speed of 5 - 16 W / min until the power of the modification layer material target is 40 - 400 W. The magnetron co-sputtering time is 5 - 25 min, and the time in the power overlap region is 1 - 3 min.
8. The preparation method of a gradient-varying powder material according to claim 5 or 7, characterized in that: During the process of forming the gradient layer by magnetron co-sputtering, the flow rate of argon introduced is 10 - 50 sccm; the vacuum degree is 0.1 - 1.0 Pa, the swing speed of the substrate workpiece table is 30 - 60 r / min, and the vibration frequency is 10 - 40 Hz.
9. The preparation method of a gradient-varying powder material according to claim 5 or 7, characterized in that: The gradient layer is heat-treated, and finally a modification layer is provided on the surface of the heat-treated gradient layer; the temperature of the heat treatment is 100 - 900 °C, and the heat treatment time is 10 - 90 min.
10. Use of a gradient-varying powder material according to claim 1 or 2, characterized in that: The gradient-gradient powder material is applied as a heat dissipation material for electronic devices, a high-speed cutting tool material, an abrasive and grinding tool material, and a high-temperature protection material.
Citation Information
Cited By
Nano-based wear-resistant coating material
CN121379285A
A nanobase wear-resistant coating material
CN121379285B
Composite sealing ring suitable for extreme temperature alternating working condition and forming method of composite sealing ring
CN121945776A
A composite sealing ring suitable for extreme temperature alternating conditions and its molding method
CN121945776B